Artificial Intelligence Powered Pedagogy: Unveiling Higher Educators Acceptance with Extended TAM - Kavitha, K; Joshith, V P (Journal of University Teaching and Learning Practice, 2025)
There is a growing prevalence of AI tools in the arena of higher education. The willingness and intentions of higher educators play a significant role in successfully incorporating these tools. This investigation extends the Technology Acceptance Model (TAM) to explore the multifaceted interplay among determinants shaping higher educators’ intentions for employing AI tools in their professional and pedagogical domains. The data was gathered from 400 respondents, comprising educators holding positions ranging from assistant professors to professors within Indian HEIs. The investigation validated the TAM model’s applicability using covariance-based systematic equation modeling (CB-SEM) and supported nine of the fifteen proposed hypotheses. Further, the investigation underscores the significance of fostering higher educators’ competency and confidence in AI tools through focused training and support services. Additionally, it highlights the role of their inherent openness to be proficient in such novel technological advancements. This investigation advances the prevailing AI-strengthened pedagogical sphere of education.